P40 Increased advanced glycation end products in patients with chronic obstructive pulmonary disease (COPD). (2nd December 2011) - John, M; Hussain, S; Selvarajah, S; Sayers, I; Hall, I P; Fairclough, L; Bolton, C E
Abstract : Introduction: Advanced glycation endproducts (AGE) are markers of glycaemic and oxidative stress, pro-inflammatory and alter structure through collagen cross-linking, formed through the Maillard reaction. There has been recent interest in AGE and its receptor: RAGE in airways1 and circulating2 in subjects with COPD as well as in a GWAS of lung function.3 Skin autofluoresence permits non-invasive measurement of skin AGE, validated against biopsies. Skin levels reflect accumulation, unlike circulating levels which are more variable. We hypothesised that skin AGE was increased in subjects with COPD and related to lung function. Methods Subjects >40 years, with and without COPD, all with >10 smoking pack years, were recruited. All subjects were assessed at clinical stability. Control never smokers were also recruited. Detailed history, post-bronchodilator spirometry and skin AGE were determined. Circulating AGE and soluble RAGE were measured by ELISA. Results: There were 49 COPD subjects; 18 current/ex-smokers without COPD; 16 never smokers, Abstract P40 table 1 . The mean skin AGE was greatest in subjects with COPD compared to both control groups, p<0.05, ANOVA, Abstract P40 table 1 . There was an indirect relationship between FEV1 % predicted and skin AGE, r=−0.46, p<0.01. A stepwise multiple regression was performed, with skin AGE as the dependent, and FEV1 % predicted, smoking pack years, age, BMI and gender entered into the model. FEV1 % predicted and smoking pack years were independent variables, p<0.01. There was no significant difference in serum AGE between groups. Mean soluble RAGE was lowest in the COPD subjects and significantly lower than control never smokers, p<0.05, ANOVA, Abstract P40 table 1 . Conclusions: People with COPD have increased skin AGE compared to subjects with a smoking history and control never smokers. Subjects with COPD also have decreased serum soluble RAGE levels compared to never smokers. The FEV1 % was an independent variable of skin AGE. Further research should explore the potential role of AGE in the co-morbidities of COPD.